Mevr. Letelier (links) wordt ontvangen door PvdA op congres in de RAI. Rechts: Den Uyl en vrouw - Singels, Han,
Mevr. Letelier (links) wordt ontvangen door PvdA op congres in de RAI. Rechts: Den Uyl en vrouw.